Latent Cytomegalovirus Reactivation in Patients With Liver Failure: A 10-Year Retrospective Case-Control Study, 2011-2020 - Yang, Qingluan; Zhou, Zhe; Yang, Xuefang; Chen, Yuming; Liu, Aiping; Zhang, Bingyan; Shao, Lingyun; Zheng, Jianming; Zhang, Wenhong (Frontiers in Cellular and Infection Microbiology, 2021)
Background. The aim of this study was to explore potential risk factors for cytomegalovirus (CMV) reactivation and their impact on liver failure patient outcomes. Methods. A 10-year retrospective case–control study was conducted in adult participants, who were diagnosed with liver failure and had undergone CMV DNA tests. CMV reactivation cases were matched with controls at a 2:1 ratio based on age, sex, and year of admission. Univariate and multivariate analyses were used to explore risk factors for CMV reactivation. Results. Between January 2011 and April 2020, 198 adult patients with liver failure and available CMV DNA test results were enrolled into the study. Among them, 33 patients had detectable CMV DNA in their plasma (16.7%). Clinical manifestations and liver function were comparable between the CMV reactivation and non-reactivation groups. However, CMV reactivation may triple mortality in patients with liver failure. We found that nearly 50% of patients in the CMV-positive group received glucocorticoids, compared to 13.6% in the CMV-negative group (P=0.000). The median total glucocorticoid dose included 836.5 mg of methylprednisolone (IQR 308.7-1259.0 mg) in the CMV-positive group, which was significantly higher than that in the CMV-negative group. A multivariate analysis revealed that glucocorticoid use significantly increased the risk of CMV reactivation (adjusted OR, 4.84; 95% CI, 1.61–14.49; P=0.005). Patients with CMV reactivation tended to be associated with higher white cell counts (adjusted OR, 1.21; 95% CI, 1.08–1.36; P=0.002). Conclusions. High intravenous glucocorticoid doses may be the most important risk factor for CMV reactivation in liver failure.